Abnormalities detected at pre‐purchase examination of National Hunt racehorses presented at sale. (8th September 2019) - Barrett, E.; Arkins, S.
Summary: Background: Few studies are available concerning prevalences of abnormalities in the Thoroughbred horse population. Objectives: Determine the prevalence of commonly observed abnormalities in a National Hunt Thoroughbred population using results of pre‐purchase examinations conducted at Thoroughbred sales venues. Study design: Retrospective cross‐sectional study. Methods: Veterinary pre‐purchase examination certificates for 13, 603 3‐ and 4‐year‐old Thoroughbred National Hunt horses from Tattersalls Ireland, Goffs Ireland and Doncaster Bloodstock Sales Ltd. (DBS) Sales were analysed. All conditions noted by the veterinarians were recorded to determine the prevalence of abnormalities. Results: Abnormalities were recorded in 73.6% of horses; 12.0% had abnormalities likely to prejudice their use for racing. Metacarpal/metatarsal exostoses and tarsal‐plantar desmitis affected 17.1 and 19.4% of the sample respectively, while 9.9% were found to make abnormal respiratory noises and 5.3% had recurrent laryngeal neuropathy. Age, year of birth and sex significantly affected the prevalence of many abnormalities (P<0.001). The proportions of horses sold differed significantly between horses with and without some abnormalities, with unaffected horses significantly more likely to be sold (e.g., prejudicial findings present vs. non‐prejudicial/none, 38.1% vs. 77.6% respectively, P<0.001). A range of abnormalities significantly negatively affected the price at sale (P<0.001). Significantly higher proportions of horses in the lower price categories had multiple abnormalities (P<0.001). Main limitations: The study consisted only of horses entered into store horse sales and presented for sale. Horses kept for racing or breeding purposes or horses withdrawn prior to the panel veterinary pre‐purchase examination were not included. The upper respiratory tract was only examined endoscopically in horses found to have an abnormal respiratory noise. Conclusions: A large proportion of 3‐ and 4‐year‐old Thoroughbred National Hunt horses intended for sale are affected by abnormalities. The prevalence of many abnormalities increases with age and certain abnormalities are viewed negatively by purchasers, affecting sale of the horse and achieved sale price.